Table of Content - - (Journal of engineering sciences and information technology, 2023)
Table of Content:1. Enhancing The Performance of WDM-PDM 16-QAMDr. Raghad Mohammad Fayez Alalfi, Dr. Abdulkareem Alsalem2. Effect of window width on the fire speed spread in high-rise buildingsEng. Raya Haqqi Ismail, Dr. Omar Hazim Kharufa3. Effect of Electromagnetic Field (ELF) on Humanʹs Body-ReviewAsst- Lecturer\ Ahmed Mohammed Farhan, Asst- Lecturer\ Hadeer Mohammed Farhan4. An Efficient Energy Optimization Method for 5G Networks using Integrated Optimization AlgorithmEng. Wesam Ahmad Jaradat5. The Preferences of Interior Design of the Middle-Class Families in JordanDr. Wafa Moh’d Fawaz Sinan, Prof. Demet Irkli Eryildiz
Keywords: The Journal of engineering sciences and information technology